COLLEGE STUDENTS' VIEWS ON COMPLETING THE TEST THROUGH GAME-BASED LEARNING - Sitorus, Friska Ria; Silalahi, Wolter Parlindungan; Naibaho, Pestaria (Bahasa Indonesia Prima, 2022)
Recently, game-based learning has been increasingly popular in education to increase the colleges' student participation in learning activities, especially conducting tests. This study examined the college students' learning experiences by conducting a pretest and posttest through the Kahoot application. This study recruited four college students aged twenty to twenty-two to participate who were selected purposely to provide